2021
DOI: 10.3390/ijerph18168355
|View full text |Cite
|
Sign up to set email alerts
|

Deviant Peer Affiliation and Non-Suicidal Self-Injury among Chinese Adolescents: Depression as a Mediator and Sensation Seeking as a Moderator

Abstract: Non-suicidal self-injury (NSSI) is an emerging health problem among adolescents. Although previous studies have shown that deviant peer affiliation is an important risk factor for this behavior, the reasons for this relationship are unclear. Based on the integrated theoretical model of the development and maintenance of NSSI and the social development model of delinquency prevention, this study tested whether depression mediated the relationship between deviant peer affiliation and NSSI and whether this mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…In line with this model, the association between depressive symptoms and NSSI may be moderated by some individual traits. Earlier research reported some psychological moderators (e.g., resilience, trait hope, impulsivity) moderated the relationship between negative affective states and NSSI (Jiang et al, 2018;Wei et al, 2021;Xiao et al, 2020;You et al, 2016). We extended earlier research by identifying a genetic moderator, namely the GABRA2 rs279858 genotype, in the association between depressive symptoms and NSSI.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In line with this model, the association between depressive symptoms and NSSI may be moderated by some individual traits. Earlier research reported some psychological moderators (e.g., resilience, trait hope, impulsivity) moderated the relationship between negative affective states and NSSI (Jiang et al, 2018;Wei et al, 2021;Xiao et al, 2020;You et al, 2016). We extended earlier research by identifying a genetic moderator, namely the GABRA2 rs279858 genotype, in the association between depressive symptoms and NSSI.…”
Section: Discussionmentioning
confidence: 62%
“…That is, some individual traits may moderate the relationship between negative affective states (e.g., depressive symptoms) and NSSI. This view has been supported by previous studies that identi ed several individual psychological moderators (e.g., trait hope, resilience, and impulsivity) in the association between negative affective states and adolescent NSSI (Jiang et al, 2018;Wei et al, 2021;Xiao et al, 2020;You et al, 2016). As important biological markers of individual differences, some genes may also play moderating roles in the relationship between depressive symptoms and NSSI.…”
Section: The Moderating Role Of Gabra2mentioning
confidence: 54%
See 2 more Smart Citations
“…Therefore, we assume that deviant peer affiliation should increase this risk of NSSI. Indeed, a previous study showed that deviant peer affiliation was positively correlated with NSSI among Chinese adolescents (Wei et al, 2021). In addition, the social development model (Hawkins and Weis, 1985) postulates that families, schools, peers, and communities all contribute to individual development.…”
Section: Deviant Peer Affiliation As a Potential Mediatormentioning
confidence: 99%